2010
DOI: 10.1162/biot_a_00018
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Religion: How Cognitive By-Products, Adaptive Learning Heuristics, Ritual Displays, and Group Competition Generate Deep Commitments to Prosocial Religions

Abstract: Understanding religion requires explaining why supernatural beliefs, devotions, and rituals are both universal and variable across cultures, and why religion is so often associated with both large-scale cooperation and enduring group conflict. Emerging lines of research suggest that these oppositions result from the convergence of three processes. First, the interaction of certain reliably developing cognitive processes, such as our ability to infer the presence of intentional agents, favors-as an evolutionary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
266
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(274 citation statements)
references
References 92 publications
2
266
0
6
Order By: Relevance
“…Previous research has identified both functional and dysfunctional consequences of group rituals (e.g., Atran & Henrich, 2010;Blake, 2014;Collins, 2004;Durkheim, 1912;Irons, 1996;Norenzayan & Shariff, 2008;Rossano, 2012). In contrast, we focus on the possible intrapsychic benefits of rituals for individuals, predicting that rituals can reduce anxiety for individuals about to face a performance task.…”
Section: Rituals Anxiety and Performancementioning
confidence: 98%
“…Previous research has identified both functional and dysfunctional consequences of group rituals (e.g., Atran & Henrich, 2010;Blake, 2014;Collins, 2004;Durkheim, 1912;Irons, 1996;Norenzayan & Shariff, 2008;Rossano, 2012). In contrast, we focus on the possible intrapsychic benefits of rituals for individuals, predicting that rituals can reduce anxiety for individuals about to face a performance task.…”
Section: Rituals Anxiety and Performancementioning
confidence: 98%
“…
Moralistic gods, supernatural punishment and the expansion of human sociality Benjamin Grant Purzycki 1 , Coren Apicella 2 , Quentin D. Atkinson 3,4 , Emma Cohen 5,6 , Rita Anne Mcnamara 7 , Aiyana K. Willard 8 , Dimitris Xygalatas 9,10,11 , Ara norenzayan 7 & Joseph henrich 7,12,13 Since the origins of agriculture, the scale of human cooperation and societal complexity has dramatically expanded 1,2 . This fact challenges standard evolutionary explanations of prosociality because well-studied mechanisms of cooperation based on genetic relatedness, reciprocity and partner choice falter as people increasingly engage in fleeting transactions with genetically unrelated strangers in large anonymous groups.
…”
mentioning
confidence: 99%
“…Over time, these deities spread culturally and came to dominate the modern world religions like Christianity, Islam and Hinduism. Such traditions eventually came to account for a large proportion of the world's population 6,7,13,14 (see Supplementary Information section S1). Here we directly test one specific hypothesis: conceptions of moralistic and punitive gods that know people's thoughts and behaviours promote impartiality towards distant co-religionists, and as a result contribute to the expansion of sociality.…”
mentioning
confidence: 99%
“…Indeed, many scholars have suggested that rituals are ubiquitous because they are central to the functioning of large-scale cooperative groups, forming the basis of contemporary society (Atran & Henrich, 2010;Durkeim, 1915;Irons, 1996;Norenzayan & Shariff, 2008;Rossano, 2012;. The idea of ritual regulating a person's ability to connect with others has long-standing tradition in anthropology.…”
Section: Social Regulationmentioning
confidence: 99%